ANALISIS PENGARUH PENDAPATAN USAHA DAN BIAYA OPERASIONAL TERHADAP LABA BERSIH PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Parapat, Nancy Agustinova; Siregar, Dian Lestari (SCIENTIA JOURNAL, 2022)
This study aims to analyze the effect of operating income and operating costs on net income in food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange in 2016-2020. It is known that the independent variable is operating income and operating costs, while the dependent variable is net income. The population in this study were 30 companies. Regression analysis method used is multiple linear regression analysis through classical assumption test and hypothesis testing. Based on the results of this study, it shows that thitung with ttabel is 2,947 > 1.70329, ie thitung is greater than ttabel which means operating income partially affects net income, and the results of partial test operating costs have an effect on net income with obtained thitung 3.667 > ttabel 1.70329 ,that is. thitung is greater than ttabel. The results of the study simultaneously show the value of Fhitung 40.315 > Ftabel 3.35, that is Fhitung is greater than Ftabel which means there is a simultaneous effect between income and operating costs on net income. Keywords: Revenue, Operational Cost, Net Income.